Key issues for long-pulse high-βN operation with the Experimental Advanced Superconducting Tokamak (EAST). (24th March 2017) - Gao, Xiang; Yang, Yao; Zhang, Tao; Liu, Haiqing; Li, Guoqiang; Ming, Tingfeng; Liu, Zixi; Wang, Yumin; Zeng, Long; Han, Xiang; Liu, Yukai; Wu, Muquan; et al.
Abstract: In the last few years, long-pulse H-mode plasma discharges (with small edge-localized modes and normalized beta, β N 1) have been realized at the Experimental Advanced Superconducting Tokamak (EAST). This paper reports on high- β N (>1.5) discharges in the 2015 EAST campaign. The characteristics of these H-mode plasmas have been presented in a database. Analysis of the experimental limit of β N has revealed several main features of typical discharges. Firstly, efficient, stable high heating power is required. Secondly, control of impurity radiation (partly due to interaction between the plasma and the in-vessel components) is also a critical issue for the maintenance of high- β N discharges. In addition an internal transport barrier (ITB) has recently been observed in EAST, introducing further improvement in confinement surpassing H-mode plasmas. ITB dynamics is another key issue for high- β N plasmas in EAST. Each of these features is discussed in this paper. Study and improvement of these issues could be considered as the key to achieving long-pulse high- β N operation with EAST.